Behavioural Biases and its Impact on Investment Decision- Making: A Review Based Analysis - Inderjit Kaur; Ahmad, Sultan; Rafat Fatima (International Review of Management and Marketing, 2026)
The study investigates the influence of behavioural biases on investor behaviour in financial markets, focusing on overconfidence, herding behaviour, disposition effect, anchoring, loss aversion, mental accounting, and representativeness bias. Investors often overestimate their ability to predict market movements, which may lead to speculative trading and excessive risk-taking. Such behaviour can increase trading volumes while resulting in suboptimal investment outcomes. Herding behaviour, or the tendency of investors to follow the actions of others, becomes particularly visible during periods of market downturns or financial instability. The disposition effect also affects investor decision-making, as investors tend to sell profitable assets too quickly while holding losing assets for a longer period, which can contribute to market inefficiencies. Anchoring and loss aversion further influence investment choices; investors may rely heavily on initial information when making decisions and often react more strongly to potential losses than to equivalent gains. In addition, mental accounting and representativeness bias may cause investors to evaluate investments in isolation or assume that past trends will continue in the future, leading to unbalanced investment decisions. Overall, the study highlights how behavioural biases shape investor behaviour and influence decision-making in financial markets.